2008
DOI: 10.1111/j.1463-1326.2007.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone attenuates fatty acid–induced oxidative stress and apoptosis in pancreatic β‐cells

Abstract: Pioglitazone attenuated fatty acid-induced oxidative stress and apoptosis in pancreatic beta-cells. TZDs might be used as a mean for maintaining beta-cell survival and preserving capacity of insulin secretion in patients with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Another mechanism involves direct actions on pancreatic beta cells [44]. Recent reports have demonstrated that thiazolidinediones directly improve beta cell function [45], ameliorate lipotoxicity [46] and prevent beta cell apoptosis [47,48]. In Wfs1 −/− A y /a mice, direct protective effects, as well as indirect effects, are likely to be exerted.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism involves direct actions on pancreatic beta cells [44]. Recent reports have demonstrated that thiazolidinediones directly improve beta cell function [45], ameliorate lipotoxicity [46] and prevent beta cell apoptosis [47,48]. In Wfs1 −/− A y /a mice, direct protective effects, as well as indirect effects, are likely to be exerted.…”
Section: Discussionmentioning
confidence: 99%
“…Partial recovery from palmitate and HG-induced inflammation via TLR2 and TLR4 inhibition suggests the presence of alternate NF-B inflammatory pathways. Recent data indicate that peroxisome proliferator-activated receptor (PPAR)␥ activation may be related to TLR activation supporting this process (30).…”
Section: Ajp-endocrinol Metabmentioning
confidence: 99%
“…Therefore, oxidative stress may be the central mechanism mediating glucotoxicity or lipotoxicity in pancreatic ␤-cells (31). Interestingly, TZDs also inhibit ␤-cell dysfunction induced by high levels of glucose or lipids (35,41,43). In this study, we found that Fig.…”
Section: E917 Antioxidative Effects Of Tzds In Pancreatic ␤-Cellsmentioning
confidence: 49%
“…In addition, TZDs improve islet ␤-cell function and reduce oxidative stress in islets of db/db mice (15-17). Although the expression level of PPAR␥ is quite low in islets, several reports have shown protective effects of TZDs against glucose-or lipid-induced toxicity in islets (27,35,41). These reports suggest that TZDs directly provide beneficial effects on islet ␤-cells, and the reduction of oxidative stress may play an important role in this process.…”
mentioning
confidence: 98%